Dynamic determination of optimum growth rate of listeria monocytogenes in minas soft cheese during cold shelf-life - Cadavez, Vasco (2019)
This study aimed to compare the kinetic parameters of L. monocytogenes during refrigerated shelf-life of soft Minas cheese produced with raw or pasteurised milk, and with or without addition of a cocktail of selected LAB (starter). A dynamic tertiary model based on the Huang and the cardinal parameter models, adjusted to each of the four treatments, determined that the slowest growth (0.0281 In CFU/g h-l) and the lowest carrying capacity (14. 12 In CFU/g) of L monocytogenes in Minas cheese was obtained by adding the tailored culture to raw milk.